RANCANG BANGUN SISTEM PENCARIAN INFORMASI LOWONGAN KERJA SE-WILAYAH III CIREBON BERBASIS CRM - Erlan Darmawan; Toni Khalimi (NUANSA INFORMATIKA, 2012)
Job seekers are faced with fierce competition in the world of work, and the increasing human resources. Information retrieval system design job at region III Cirebon is based CRM solution as a medium of information search in the design for job seekers who want to work in the area CIAYUMAJAKUNING (Cirebon, Indramayu, Majalengka and Kuningan), where job seekers can search for other than work, they can also apply for jobs online, with their resume processing the data, without having to print out resume and send to the company that it chooses, while for companies that outsource, the company can see and accept applications from applicants online, so companies can find workers according to criteria of quality jobs. The methodology used in the construction of this system using the prototype, where prototyping is the process of modeling a simple software that allows users to have a basic overview of the program and initial testing. In the construction of a new business concept that provides job information as region III Cirebon, then carried the implementation of a strategic approach to CRM (Customer Relationship Management) that focuses on information services to customers, in achieving CRM first and second classification, is reached new customers, and retain existing customers. This service is packaged with the creation of websites used PHP as the programming language and MySQL as the database used.Keywords : Build Design, Jobs, Region III Cirebon, CRM